Foundations for youth ministry : theological engagement with teen life and culture - Borgman, Dean, 1928- (Grand Rapids : Baker Academic, 2013)
"Dean Borgman, a nationally known youth ministry expert, offers a new edition of his influential classic. Reaching a broadly ecumenical audience, this book challenges readers to think about the theological nature of youth ministry. Questions for discussion and reflection are included. This thoroughly updated edition was previously published as When Kumbaya Is Not Enough" -- Publisher description.
Pt. 1. Practical theological foundations. Introducing a theology for youth ministry -- The art of interpretation -- The practice of interpretation -- Basic theology for youth ministers -- From general theology to practical theology for youth ministry -- Pt. 2. Theology of persons -- theology of growth and development -- Theology of personhood and community -- Theology of family and peers -- Theology of sexuality -- Pt. 3. Practical theology engaging culture -- Theologizing about culture and cultures -- Relating to Christ in culture -- Practical theology in a digital age -- Theology and ministry in a consumerist age -- Funny theology? -- Pt. 4. Practical theology for holistic youth ministry -- Where practical theology meets holistic ministry -- The high calling of ministry with youth.
Rev. ed. of: When Kumbaya is not enough : a practical theology for youth ministry. c1997.
Includes bibliographical references and index.
Keywords: Church work with youth